Orthogonal Wettability of Hierarchically Textured Metal Meshes as a Means of Separating Water/Oil Emulsions1 . Issue 5 (8th February 2017) - O'Loughlin, Thomas E.; Martens, Sean; Ren, Suchang Roy; McKay, Patrick; Banerjee, Sarbajit
Abstract : The removal of submicrometer‐sized oil droplets from water remains a key challenge in engineering the separation of emulsions and has emerged as an urgent imperative given the increasing use of unconventional extractive processes. In this work, the authors demonstrate that a substrate with hierarchical texturation shows pronounced differences in the wettability of water and hexadecane, thereby, facilitating the separation of these two disparate liquids at room temperature and pressure. The multiscale textured substrates are assembled using a facile and readily scalable process, wherein ZnO nanotetrapods are spray‐deposited onto a steel mesh with micron‐sized features. Separation efficiencies well over 99% are accessible by simply flowing emulsions across these hierarchically textured surfaces. Abstract : Hierarchically textured surfaces comprising steel meshes coated with ZnO nanotetrapods effectively separate the oil and water components of emulsions based on differential wettability at ambient temperature and pressure in a facile flow process. A scalable method allowing for greater than 99% separation efficiency has been realized for mechanical resilient substrates, paving the way to largescale industrial applications.